Examining The Role Of Social-Cultural Capital In Youth Entrepreneurship : A Comparative Study Between Malaysia And Laos - L. Karuppiah Pillay, Tharuma Rajan Pillai (2018)
This comparative study explores the role of social-cultural capital in youth entrepreneurship through social network between the efficiency-based economy of Malaysia and the factor based economy of Laos/Lao PDR.Two non-homogenous sovereign contexts are compared to unveil the potent role of social-cultural capital in youth entrepreneurship through social network dynamics.Central to this discussion is the Theory of Social Network with its emphasis on network structure,type and ties coupled with social context within the theoretical frameworks of Bourdieu,Coleman and Putnam etc.A qualitative case study research approach was employed through the strategy inquiry tools of in-depth interviews and focus groups studies in analysing youth entrepreneurship contexts and contents.This preferred approach is focused on garnering in-depth information: thematically rich with meaningful interpretation and significant application.Furthermore, case study method encapsulates,demarcates and facilitates diverse cases for comparison between two sovereign contexts through a comprehensive case study protocol.Key findings emerging from thematic pattern at synthesis level include:the emergence of two tier prominent categories,with the first tier codes such as family members and entrepreneurial ecosystem governing the stimulating or stifling factor of social-cultural capital on youth entrepreneurship,both in Malaysia and Laos.The second tier codes unveil the role of value system, acquaintance,informal groups,culture and community in supporting first tier codes in the actualization of youth entrepreneurship.The ancillary codes such as technology and social media equally affect the governing and second tier codes in influencing youth entrepreneurship.Three types of primary network system are unveiled through the collaboration of these prominent codes and categories including privileged,preferred and laissez faire networks,which dynamically intermingle with four types of social context network ties.The outcome of this study contributes theoretically in asserting the likelihood of comparing two non homogenous socio-economic contexts in determining the role of social-cultural capital through social network in youth entrepreneurship,at micro-,meso- and macro- level.From practical perspective,this study reveals the capability of social-cultural capital in opening up pathways to the avenues of financial,physical, human and knowledge capitals,making it applicable to the broader regional context of ASEAN which is made up of factor-,efficiency and innovation- based economies. Further research study is recommended in exploring the possibility of two different sovereign socio-economic contexts sharing the capability of social network system in influencing youth entrepreneurship beyond the pursuit of uniformity in economic status or development.